Corporate social responsibility and dividend policy - Cheung, Adrian; Hu, May; Schwiebert, J. (Wiley-Blackwell Publishing Asia, 2016)
This study outlines and tests two corporate social responsibility (CSR) views of dividends. The first view argues that firms are likely to pay fewer dividends because CSR activities lower the cost of equity, encouraging firms to invest or hoard cash rather than to pay dividends. The second view suggests that CSR activities are positive NPV projects that increases earnings and hence dividend payouts. The first (second) view predicts that firms with a stronger involvement in CSR activities should be associated with a lower (higher) dividend payouts. The finding supports the second view and is robust.